Correlations between coagulation abnormalities and inflammatory markers in trauma-induced coagulopathy - Wen, Ke; Lin, Zhexuan; Tan, Haizhu; Han, Ming (Frontiers in Physiology, 2024)
Introduction: In multiple trauma patients, the occurrence of trauma-induced coagulopathy (TIC) is closely associated with tissue damage and coagulation function abnormalities in the pathophysiological process. Methods: This study established a multiple trauma and shock model in Sprague-Dawley (SD) rats and comprehensively utilized histological staining and radiographic imaging techniques to observe injuries in the intestine, liver, skeletal muscles, and bones. Monitoring activated partial thromboplastin time (APTT), platelet (PLT) count, respiratory rate, blood pressure, and other physiological indicators revealed time-dependent alterations in coagulation function and physiological indicators. Enzyme-linked immunosorbent assay (ELISA) measurements of inflammatory factors Tumor Necrosis Factor-alpha (TNF-α), Interleukin-6 (IL-6) and vascular endothelial injury marker (Syndecan-1) were also conducted. Results: Experimental results demonstrated significant changes in tissue structure after multiple traumas, although widespread necrosis or hemorrhagic lesions were not observed. There were time-dependent alterations in coagulation function and physiological indicators. ELISA measurements showed a strong positive correlation between the significant decrease in PLT count and the increase in TNF-α and IL-6 concentrations. Discussion: The study provides crucial information for the early diagnosis and treatment of TIC. The findings suggest that structured monitoring of coagulation and inflammatory indicators can help in understanding the pathophysiological changes and aid in the management of TIC in multiple trauma patients.